Musical chairs: selected questions of burden-sharing in international refugee law - Gregusson Svartdal, Fridtjof (Department of Private Law, 2018)
The number of refugees worldwide has never been higher, with an estimate of 65.3 million forcibly displaced persons by the end of 2015. The brunt of the material, economic and social burdens these waves of often destitute persons represent is borne by a minority of closeproximity States, ill-equipped to handle mass influxes of people in dire need of protection and assistance. This dissertation explores the legal obligations of States to share the burden of international refugees, through four select research questions. Firstly, the existence of universal and regional obligations to burden-share are examined. Secondly, the legality of the 'third safe country' notion is examined under international law. Thirdly, the economic responsibilities of refugee-generating States towards refugees, asylum States and the UNHCR is examined. Fourthly, the obligations of States to rescue asylum seekers in distress at sea, and to process their asylum claims is examined. The fundamental observation of the dissertation is that although the 1951 Convention provides a generous set of rights to persecuted persons, its primary shortcoming in the context of this dissertation, is the lack of a clear and positive obligation, ensuring a fair distribution of the burdens of refugees between the signatory States. However, regional efforts do, to a degree, mitigate this issue by establishing obligations which seek to distribute the costs and burdens of refugees.